MAKNA SIMBOL UBARAMPÉ PADA FOLKLOR BERBENTUK TRADISI KELEMAN DI DUSUN MENUNGGAL DESA SEKARGADUNG KECAMATAN PUNGGING KABUPATEN MOJOKERTO - Khamdiyah, Ilmiyatul; Irawan, Ahmad Dani (Universitas Negeri Surabaya, 2024)
Abstrac Javanese culture that is still preserved in accordance with the development of the times has various forms in the form of traditions, rituals, capitations and temples. One of the things that belongs to culture is folklore. Of all the traditions that exist on the island of Java, there is one tradition, namely the tradition which is part of semi-oral folklore because it contains customs, people's holidays, and folk customs. The keleman tradition is one of the traditions in Mojokerto regency related to rice planting as a form of gratitude waiting for the rice to start growing content. In this keleman tradition, there is an interesting ubarampe to study more deeply the meaning of its symbol. The purpose of this study is to find out the meaning of the umbarape symbol in the keleman tradition. This study uses a qualitative descriptive method by describing, depicting, explaining, explaining and answering in more detail the problem to be studied, namely the meaning of the umbarape symbol by studying as much as possible an individual, a group or an event. Umbarape is one of the important things and must be present when carrying out the keleman tradition. Keyword: folklore, symbols, umbarape, keleman